2014
DOI: 10.1177/1355819614543161
|View full text |Cite
|
Sign up to set email alerts
|

Why public trust in health care systems matters and deserves greater research attention

Abstract: Considering the underlying importance of trust, there is too little research into the understanding, protection and recovery of trust in health care systems, not only for the effective functioning of health care systems but also for society in general. Several researchers have pointed towards a contemporary crisis of trust in health care systems and there have been many examples that show the severe effects of mistrust. More research into public trust in health care systems could contribute to improving effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
112
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(115 citation statements)
references
References 21 publications
2
112
0
1
Order By: Relevance
“…More broadly, it has been long recognized that trust often plays a central role in medical decision making, with an individual or patients' degree of trust affecting willingness to seek care, adherence to treatment recommendations, and acceptance of recommended treatment. [29][30] In the cases of vaccines and vaccination, McCauley et al 24 found that among parents who indicated they followed vaccine recommendations, 63.1% reported being "very confident" and 35.5% reported being "somewhat" confident in the safety of childhood vaccines, while among parents not following vaccine recommendations, 25.8% reported being "very confident," 51.0% reported being "somewhat" confident, and 14.2% were "not very confident." More recently, Weiner et al's 23 survey of 200 first-time expectant mothers who were in their second or third trimester of pregnancy found those planning to comply with the recommended immunization schedule for their infants had the highest levels of confidence in vaccine effectiveness, value and safety compared to mothers who were planning to delay or decline some recommended vaccines or who were unsure of their immunization plans.…”
Section: Introductionmentioning
confidence: 99%
“…More broadly, it has been long recognized that trust often plays a central role in medical decision making, with an individual or patients' degree of trust affecting willingness to seek care, adherence to treatment recommendations, and acceptance of recommended treatment. [29][30] In the cases of vaccines and vaccination, McCauley et al 24 found that among parents who indicated they followed vaccine recommendations, 63.1% reported being "very confident" and 35.5% reported being "somewhat" confident in the safety of childhood vaccines, while among parents not following vaccine recommendations, 25.8% reported being "very confident," 51.0% reported being "somewhat" confident, and 14.2% were "not very confident." More recently, Weiner et al's 23 survey of 200 first-time expectant mothers who were in their second or third trimester of pregnancy found those planning to comply with the recommended immunization schedule for their infants had the highest levels of confidence in vaccine effectiveness, value and safety compared to mothers who were planning to delay or decline some recommended vaccines or who were unsure of their immunization plans.…”
Section: Introductionmentioning
confidence: 99%
“…Within the health context, it has increasingly been associated with discussions about the quality of care, since it potentially captures something of the non-technical, inherently interpersonal nature of healthcare delivery1 [1, 2]. In the UK, recent shocking, high-profile examples of neglect in hospital wards and care homes have been drawn on by many to illustrate some of the unintended consequences of setting institutional targets and adopting financial incentives designed to increase the efficiency of the health service.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, both media reporting and official investigations have employed a bundle of terms, including compassion, empathy, care and trust, to contrast with organisational values associated with financial and bureaucratic rationalism (see for example, [3]). Trust has thereby come to represent one of the crucial dimensions of health service delivery said to potentially escape the domination of bureaucratic, administrative and market values [2]. …”
Section: Introductionmentioning
confidence: 99%
“…Prominent examples in the UK National Health'Care.data' aims to collect and share information about individuals' care to improve the 48 quality of care for all. Yet the initiative, which would link hospital and general practice 49 patient data anonymously at the individual level, has struggled to win public acceptance in the 50 face of concerns about the trustworthiness of the programme to keep sensitive information 51 secure and the potential for commercial gain to be made from patients' personal data ( research, a number of terms are used interchangeably to describe trust other than at the inter-59 personal level (Gille et al, 2015). We will use the term most widely used in the mass media 60 and scholarly writing in this context, namely, public trust.…”
mentioning
confidence: 99%
“…Examples of health care system activities where public trust matters most obviously 27 are vaccination coverage, health care provider choice, the use of the internet to identify health 28 related information, or participation in biomedical research (Gille et al, 2015;Green, 2004; 29…”
mentioning
confidence: 99%